2022
DOI: 10.1051/limn/2022006
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in Oligochaeta species composition in an anthropized stretch of a Neotropical urban river

Abstract: Aquatic environments in urban centers suffer constantly from changes in limnological variables, mainly due to increased pollution in these systems. Aquatic Oligochaeta are bioindicators of environmental change. The Iguaçu River is the second most polluted river in Brazil and in the Middle Iguaçu region is used for the public water supply. Efforts to understand the dynamics and conservation of this river are necessary, since this region has a gap in studies with aquatic invertebrates. Thus, the aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…In comparison to the other study sites, the S2 was described as an agriculture site, so it is predicted that the agriculture drainage involved pesticides and fertilizer. This is an acceptable reason to restrict the number of species or diversity on this site [19,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to the other study sites, the S2 was described as an agriculture site, so it is predicted that the agriculture drainage involved pesticides and fertilizer. This is an acceptable reason to restrict the number of species or diversity on this site [19,23].…”
Section: Resultsmentioning
confidence: 99%
“…Samples where Oligochaete worms were collected monthly from four sites along AL Shatt Al-Hillah, in the middle of Iraq, Figure 1 between October 2019 and June 2020, During the research, an Ekman dredge (15X15cm) was utilized to collect surface bottom sediment samples, which were then rinsed with water and passed through 0.2 m mesh size sieves in the field before being transported to the laboratory. In the laboratory, oligochaete worms were hand-picked from sediments using a dissecting microscope at 10x magnification, and then kept in 70% alcohol [19]. To make a temporary slide, a drop of polyvinyl lactophenol was placed on a microscopic slide.…”
Section: Methodsmentioning
confidence: 99%
“…35 However, Tonin et al 36 suggest that, in many lakes, the increase of dissolved organic carbon (DOC) may affect the resource quality and the bioavailability of metallic elements for phytoplankton, which is not conducive to the growth of zooplankton. Pang et al 37 and Rosa et al 38 also suggested considerable negative correlations between organic matter content and species composition diversity. Hence, the sources of DOM and its degradability play an important role in regulating the nutrient level and structure of the food web in lakes, and the relationships between the two need to be elucidated urgently.…”
Section: Introductionmentioning
confidence: 94%
“…No caso do rio Pintado, as alterações físicas na vegetação ripária e na forma do canal, são decorrentes da ocupação das margens para residências urbanas, terras agrícolas e mineração. Além das alterações físicas no rio, essas atividades contribuem potencialmente com esgoto não tratado, fertilizantes e pesticidas, e podem interagir com a biota aquática, através da teia trófica, aumentando o risco ecológico para o ecossistema 5,6 . A preocupação com esse afluente da bacia do Iguaçu aumenta porque há uma lacuna sobre sua ictiofauna.…”
Section: Introductionunclassified